Adapting 'lesson study' to investigate classroom pedagogy in initial teacher education: what student-teachers think. Issue 1 (2nd January 2016) - Cajkler, Wasyl; Wood, Phil
Abstract : This paper reports findings from a project that explored the use of a modified form of 'lesson study' in a one-year programme of secondary school initial teacher education (ITE). Twelve mentors and student-teachers worked in pairs to design and teach two 'research lessons' in the course of two eight-week teaching practice placements as part of a university–school partnership for the preparation of new teachers. Participating student-teachers reported that engagement in this form of lesson study with a mentor was an effective way to help them grow individual teaching skills, knowledge and confidence in teaching placements. In addition, in most cases, it enabled active and creative participation in a community of teacher learners. However, engagement in lesson study not only supported student-teachers to meet 'qualifying to teach' standards, but also offered opportunities for holistic study of teaching and learning, leading to growth in what we characterise as 'pedagogic literacy'.